The classification of EEG-based wink signals: A CWT-Transfer Learning pipeline - Jothi Letchumy, Mahendra Kumar; Rashid, Mamunur; Musa, Rabiu Muazu; Mohd Azraai, Mohd Razman; Norizam, Sulaiman; Rozita, Jailani; Anwar, P. P. Abdul Majeed (Elsevier, 2021)
Brain–Computer Interface technology plays a vital role in facilitating post-stroke patients’ ability to carry out their daily activities of living. The extraction of features and the classification of electroencephalogram (EEG) signals are pertinent parts in enabling such a system. This research investigates the efficacy of Transfer Learning models namely ResNet50 V2, ResNet101 V2, and ResNet152 V2 in extracting features from CWT converted wink-based EEG signals, prior to its classification via a fine-tuned Support Vector Machine (SVM) classifier. It was shown that ResNet152 V2-SVM pipeline could achieve an excellent accuracy on all train, test and validation datasets.